QUANTUM CHEMICAL DESIGNING OF TRIPHENYLAMINE DYES WITH D-A-Π-A CONFIGURATION FOR DYE SENSITIZED SOLAR CELLS: MOLECULAR ENGINEERING THROUGH FIRST-PRINCIPLES CALCULATIONS - Ashraf Janjua, Muhammad Ramzan Saeed (Journal of the Chilean Chemical Society, 2018)
In this research article, we have designed triphenylamine (TPA) dyes with D-A-π-A structure and their electro-optical and charge injection properties have been calculated. The computational techniques are used to study the effect of additional acceptor in π-conjugated systems on absorption spectra and electron injection of the dyes. All the dyes have shown absorbance in visible region. The effect of additional acceptor on the performance of sensitizers in dye sensitized solar cells has also been determined. In theoretical examination electron injection efficiency (Фinject.) and light harvesting efficiency (LHE) have been calculated. The results indicate that the combination and selection of appropriate conjugated bridge in dye sensitizer is an important way to design efficient dyes.